2022
DOI: 10.14309/ajg.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

The Real-World Effectiveness and Safety of Ustekinumab in the Treatment of Crohn's Disease: Results From the SUCCESS Consortium

Abstract: INTRODUCTION:We evaluated the real-world effectiveness and safety of ustekinumab (UST) in patients with Crohn's disease (CD).METHODS:This study used a retrospective, multicenter, multinational consortium of UST-treated CD patients. Data included patient demographics, disease phenotype, disease activity, treatment history, and concomitant medications. Cumulative rates of clinical, steroid-free, endoscopic, and radiographic remissions were assessed using time-to-event analysis, and clinical predictors were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
16
1
2
Order By: Relevance
“…In the SUCCESS trial, patients with biologic exposure experienced significantly reduced rates of radiographic remission at 12 months compared to biologic-naïve patients. 14 However, there were no differences in prior biologic therapy between the TH and no-TH group in our study ( p = 0.678). Prior usage of biologics was also not associated with likelihood of TH in patients at W26 ( p = 0.404).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In the SUCCESS trial, patients with biologic exposure experienced significantly reduced rates of radiographic remission at 12 months compared to biologic-naïve patients. 14 However, there were no differences in prior biologic therapy between the TH and no-TH group in our study ( p = 0.678). Prior usage of biologics was also not associated with likelihood of TH in patients at W26 ( p = 0.404).…”
Section: Discussioncontrasting
confidence: 58%
“… 13 , 30 Another real-world clinical study (SUCCESS trial) showed that 30% of patients with CD achieved radiographic remission at 12 months after UST treatment. 14 In our study, only 18.9% patients achieved TH at W26 of UST therapy. The lower rates of TH in our study were due to the shorter follow-up time and the different definitions.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Although the efficacy and safety of ustekinumab treatment in CD has been well established, 7 there is still limited data regarding its use in patients with impaired renal function. As an IgG monoclonal antibody, ustekinumab clearance is governed primarily by intracellular catabolism mechanisms and is not depended on glomerular filtration or enzymatic degradation by the liver 8 .…”
Section: Discussionmentioning
confidence: 99%